ASBAB AL-WURUD AS AN APPROACH TO UNDERSTANDING THE PURPOSE OF HADITH (MAQASID AL-SUNNAH) IN A WASATIYYAH AND BALANCED WAY THAT IS PRACTICED IN CONTEMPORARY SOCIETY - Masruri, Muhammad; Sahimi, Mohd Shafiq; Karim, Abdul; Ahmad, Shakila (RGSA, 2024)
Objective: The understanding and implementation of the Hadith, as the second main source in Islam, should align with the intended purpose and message delivered by the Hadith to its audience. To preserve the peace of humanity, one of these qualities involves being balanced, moderate, and not extreme. Currently, there are still a significant number of Muslims who excessively adhere to the Hadith of the Prophet, exhibit harsh behavior from a liberal perspective, or solely rely on logical reasoning. Theoretical framework: This article seeks to elucidate the application of maqasid al-Sunnah in the interpretation of the Hadith of the Prophet SAW, employing the methodologies established by renowned scholars as well as the method of asbab al-wurud in a balanced and moderate manner. Method: This article uses content analysis to examine discussions on the method of asbab al-wurud as an approach to maqasid al-sunnah. This method is used to interpret hadith in a comprehensive and balanced way. Results and Discussion: Attaining equilibrium and unity in life is one of the primary objectives of the observance of the Hadith of the Prophet. To achieve this objective, it is necessary to comprehend the Nabawi Hadith in a straightforward and equitable manner, aligning with its intended purpose and objective. The understanding and interpretation of a hadith, as well as its transmission to the listener, can be obtained by consulting the scholarly opinions of the Salf al-Salih and considering the asbab al-Wurud. Conclusion: The concept of maqasid al-sunnah, when understood through the lens of the ultimate hadith and the application of the method of asbab al-wurud, allows for a more comprehensive and balanced comprehension of a hadith. This approach ensures that the hadith is interpreted in a manner that is in line with the conditions of the current times and places, and is accepted by all Muslims. This strategy enables the effective management and regulation of extreme, excessively literal, and radical comprehension, resulting in the attainment of peace and wellbeing for all of humanity.